Forecasting Sales 3 Kg Lpg Using Single Exponential Smoothing Method - Aini Nur Aini; Rani Purbaningtyas; R Dimas Adityo (JEECS (Journal of Electrical Engineering and Computer Sciences), 2017)
Forecasting is a very important in corporate strategy planning. Single Exponential Smoothing Method is one of thetime series forecasting methods. The purpose of this study is the number of selling period can be subsequent profitscan be sold to customers with appropriate obtained CV. Damayanti every month. This research uses selling dataobtained by selling 3kg LPG for 7 years from january 2009 until December 2016. The result of this forecasting isdone by Single Exponential Smoothing method with the result of error calculation and selected forecasting resultwhich has minimum MAE. The alpha value is the smallest MAE result = 0.9: 2534.26 from the 3kg lpg salesforecast. The alpha value used affects the results of different forecasts. Then the result of the prediction of each baseor region has a smoothing value that is setabil, up, down its value of forecasting results.